Urban environment and the psyche of citizens – mutual reflection - Al-Hmoud, Muhammad Abdallah; Merry , Anna; Ghazi Naouri, Diab; Ababneh, Amin (project baikal, 2025)
Global urbanization is forcing large numbers of people to move from traditional ways of life to life in a modern city. Powerful information flows and urban dynamics contribute to the development of mental disorders. The structure of the traditional Arab city prevented the growth of mental overload. As a result, the stigmatisation of mental disorders – treating them as a curse or a contagious disease – has taken root in traditional Arab culture. The westernisation of modern Arab cities has been accompanied by the dual effects of simultaneously increasing mental overload and eroding its stigmatisation.